1988
DOI: 10.1103/physreva.38.2883
|View full text |Cite
|
Sign up to set email alerts
|

Slow-wave electron cyclotron maser

Abstract: The basic physics of a slow-wave electron cyclotron maser (ECM) operating in the Cherenkov regime is considered. This device has the advantage over fast-wave ECM's in that it can be operated with direct axial injection of the electron beam, thus allowing for better control over beam quality and a potentially more compact design. The nonlinear evolution and saturation of the instability are studied using computer simulation. It is shown that high efficiency is attainable and, furthermore, that beam momentum spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In addition, application is restricted to a cold mono-energetic particle distribution only. Extensions have been given to loss-cone distributions by Lau and Chu (1983) and to spiraling magnetic-field aligned electron beams by Kho and Lin (1988).…”
Section: Phase Space Bunching Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, application is restricted to a cold mono-energetic particle distribution only. Extensions have been given to loss-cone distributions by Lau and Chu (1983) and to spiraling magnetic-field aligned electron beams by Kho and Lin (1988).…”
Section: Phase Space Bunching Mechanismmentioning
confidence: 99%
“…Whether the amplified slow wave can escape from the plasma is a different one and -is difficult to answer. Analytical and numerical calculations have been presented by Kho and Lin (1988) for the slow wave in a field-aligned beam plasma system and γ 0 = 2, ω ce = 2ω pe finding a strong instability. It seems that the slow wave can be more easily be made unstable when a beam along the magnetic field is present in the plasma.…”
Section: Radiation and Absorption In Bunchingmentioning
confidence: 99%
“…Kho and Lin [33] analyzed an invariant of motion of a single electron in fast and slow EM waves without using linear approximation. Their results showed that, in fast wave devices, the EM field obtains energy only from of the electrons.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the operation of CRMs when both the Cherenkov and anomalous Doppler cyclotron resonance conditions take place simultaneously have been studied in [23]- [25]. (The case of the cyclotron resonance under the anomalous Doppler effect is often called the cyclotron Cherenkov resonance.)…”
Section: Introductionmentioning
confidence: 99%